Investigation of the effect of nitrogen capture system using modified zeolites on a diesel engine in terms of performance and exhaust emissions - Hazar, Hanbey; Firat, Selahattin Ozgur; Sevinc, Huseyin (Elsevier Sci Ltd, 2025)
In this study, a novel method was developed to reduce exhaust emissions and enhance the performance of diesel engines through continuous oxygen enrichment. Unlike conventional approaches relying on oxygen cylinders, a PSA-based nitrogen filtration system was integrated into the engine to supply oxygen-enriched air in real-time. The system utilizes clinoptilolite-type zeolites modified via acid treatment and ion exchange processes using calcium and lithium ions. When unmodified, acid, calcium and lithium zeolites were placed in nitrogen filter system, it was found that the air at the outlet of the device contained 21 %, 23.2 %, 23.7 % and 24.3 % oxygen, respectively. After the integration of nitrogen filter system into the engine, carbon monoxide, hydrocarbon, and smoke density decreased and nitrogen oxide emissions increased. Moreover, enhancement in the engine torque, in-cylinder pressure, brake thermal efficiency, exhaust gas temperature, vibration and noise values were observed. Brake-specific fuel consumption decreased. Due to the use of lithium modified zeolite, which provides the highest oxygen enrichment, carbon monoxide, hydrocarbon and smoke density were reduced by 12.5 %, 8.6 % and 9.4 %, respectively. On the other hand, nitrogen oxide emission, torque and brake thermal efficiency values increased by 8.3 %, 4.9 % and 3.7 %, respectively.
Keywords: Diesel engine; Exhaust emissions; Engine efficiency; Clinoptilolite zeolite; Oxygen enrichment